Nitrogen removal by a novel heterotrophic nitrification and aerobic denitrification bacterium Acinetobacter calcoaceticus TY1 under low temperatures. (June 2022) - Wu, Linhui; Ding, Xiaoyu; Lin, Yan; Lu, Xingshun; Lv, Hang; Zhao, Manping; Yu, Ruihong
Graphical abstract: Highlights: Isolation of a novel bacterial strain Acinetobacter calcoaceticus TY1. HN-AD strains simultaneously convert ammonium, nitrite, and nitrate. Strain TY1 performed heterotrophic nitrification and aerobic denitrification. High-efficiency denitrification performance of strain TY1 at low temperatures. Abstract: A new bacterial strain, Acinetobacter calcoaceticus TY1, was identified in activated sludge. This strain efficiently metabolized nitrogen from ammonium at low temperatures, utilizing NH4 + -N, NO3 – -N, and NO2 – -N as nitrogen sources. Of these, NH4 + -N was superior in terms of both assimilation and heterotrophic nitrification at 8 °C. The nitrogen metabolism-associated genes amoA, nirK, and nosZ were identified in TY1. Optimal requirements for growth and nitrogen removal were pH 7, shaking speed of 90 rpm, a C/N ratio of 10, and sodium citrate for the carbon supply. The ability to denitrify at low temperature suggests TY1′s potential for wastewater management.